SMA Therapy in Poland: New Hopes and Challenges - Iwona Welian; Karolina Gendek; Ilona Jastrzębska; Karolina Maliszewska; Magdalena Chrościńska-Krawczyk (Kazimierz Wielki University, 2023)
Abstract: Spinal muscular atrophy (SMA) is a genetically inherited disease whose symptoms appear in children at a fairly early age. The main cause of the disease is a mutation of the SMN1 gene, which causes the lack of production of SMN This results in the disappearance of motoneurons, which consequently leads to the disappearance of the patient's ability to move and his death. An important element of coping with the disease is its early detection in newborn screening, because the earlier we start the drug, the greater the chance that the patient will maintain motor efficiency. The article describes treatment options for children in Poland, i. e. the use of such drugs as Nusinersen, which increases the amount of SMN protein, gene therapy Onasemnogen aeparvovec, which increases the amount of SMN gene, Ridisplam, which increases the amount of SMN protein, and salbutamol, which helps patients to breathe. The article also provides information about new drug therapies for the treatment of SMA and the stage of clinical trials at which they are currently being developed. It is important to look for new solutions in the treatment of SMA. Objective: To familiarize the readers of the article with the problems of SMA treatment in Poland, as well as to broaden their knowledge of new available drugs for the treatment of this disease.